Former Yugoslav Republic of Macedonia : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
The emergency nature of many of the measures taken to meet the challenges which Macedonia has faced in recent years, including the Kosovo crisis and the recent threat to the country's security, has contributed to a general laxity in the enforcement of the country's laws, including the LPP. Compliance with the procurement law has been further undermined by the absence of the institutional machinery necessary to support implementation, particularly an authoritative body to oversee enforcement and provide institutions operating under the law with guidance on its application. Whilst the Ministry of Finance (MOF) is formally charged with authority over public procurement, it is only recently that MOF has dedicated resources to perform key oversight functions. That said, the MOF unit charged with this onerous obligation, the Public Procurement Division of the Ministry's Legal Department, lacks the stature and capacity to discharge its functions effectively. Furthermore, the institutions which should play an indispensable role in performing oversight of public procurement, including the State Auditor's Office, have not yet been operating effectively. Weak enforcement is further exacerbated by a low level of awareness of the law's provisions, the roots of which lie partly in inadequate dissemination, and by the absence of sufficient numbers of public officials trained in procurement, a shortcoming which is particularly acute in self-governing units of local government. Most public officials who carry out procurement are inexperienced and lack the procurement-specific training necessary to apply the law accurately. There is also a severe problem of excessive political interference in contract award decisions in Macedonia. This is not only invited by the absence of an effective oversight institution but is, in fact, formalized by the common practice, enshrined in the LPP, of assigning to high-ranking political officials, in particular Ministers, the authority to award procurement contracts. The assessment also found evidence of many bad practices which are routinely applied to procurement in Macedonia. Principal among these is that, instead of providing bidders with formal, written bidding documents, public purchasers often only advertise an invitation to bid in a local newspaper as the sole means for soliciting bids. Such advertisements regularly include the cost estimate for the contract being tendered, the publication of which may facilitate collusion and price-fixing among bidders. Other practices which obstruct transparency include failing to disclose bid evaluation criteria to bidders in advance, the widespread use of subjective methods of evaluating bids and over-use of an "accelerated procedure" provision in the LPP, by which the period allowed to bidders to prepare their bids may be reduced from 36 days to 15 days or less. This is clearly open to manipulation by purchasers who want to give an unfair advantage to a favored bidder. Several more examples of bad practices identified by the assessment are provided in Section 2 of this report, with detailed recommendations to address them presented in Section 2.3. In order to address these weaknesses, this report recommends a number of short- term measures, designed to plug the most pressing gaps in Macedonia's national public procurement system, combined with longer-term recommendations aimed at more wide-reaching reform and development of the legal and institutional framework for procurement.